2021
DOI: 10.3390/cancers13164073
|View full text |Cite
|
Sign up to set email alerts
|

Urinary PGE-M in Men with Prostate Cancer

Abstract: Urinary PGE-M is a stable metabolite of prostaglandin E2 (PGE2). PGE2 is a product of the inflammatory COX signaling pathway and has been associated with cancer incidence and metastasis. Its synthesis can be inhibited by aspirin. We investigated the association of PGE-M with lethal prostate cancer in a case–control study of African American (AA) and European American men. We measured urinary PGE-M using mass-spectrometry. Samples were obtained from 977 cases and 1022 controls at the time of recruitment. We app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For instance, a metabolite of prostaglandin E 2 (PGE 2 ), a major proinflammatory mediator, is increased in urine of smokers [ 15 ]. It is also associated with a risk of many types of cancer in human, including colorectal, gastric, and prostate cancer [ 9 , 11 , 18 ]. Our group also demonstrated that the urinary level of a prostaglandin D 2 (PGD 2 ) metabolite reflects the severity of the food allergic symptoms in human and mice [ 8 , 13 ].…”
mentioning
confidence: 99%
“…For instance, a metabolite of prostaglandin E 2 (PGE 2 ), a major proinflammatory mediator, is increased in urine of smokers [ 15 ]. It is also associated with a risk of many types of cancer in human, including colorectal, gastric, and prostate cancer [ 9 , 11 , 18 ]. Our group also demonstrated that the urinary level of a prostaglandin D 2 (PGD 2 ) metabolite reflects the severity of the food allergic symptoms in human and mice [ 8 , 13 ].…”
mentioning
confidence: 99%